(untitled) (Western European Journal of Medicine and Medical Science, 2024)
The preceding work has been centered on the investigation of thyroid hormone within the serum of 109 patients with thyroid diseases between the ages of 12 and 50 years old, as well as 114 healthy persons of the same age and gender who served as the control group for the entirety of this clinical investigation. Included in this work are the measurement the levels of thyroid hormones TSH,T3,T4 in the serum of patients and the control group by employing the enzyme-linked fluorescence assay (ELFA) technique on the Minividas equipment. It was determined by the findings that there were thyroid disorders, which were divided into two distinct categories